A Depression Containing CO2-Enriched Water at the Bottom of Lake Monoun, Cameroon, and Implications for the 1984 Limnic Eruption - Ohba, Takeshi; Oginuma, Yu; Saiki, Kazuto; Kusakabe, Minoru; Issa,; Fouepe, Takounjou A.; Ntchantcho, Romaric; Tanyileke, Gregory; Hell, Joseph V. (Frontiers in Earth Science, 2022)
In this study, we investigated the detailed lake bottom topography to elucidate the mechanism of the 1984 limnic eruption at Lake Monoun in Cameroon. Lake Monoun was formed from three basins: west, central, and east basins. Three small depressions were found at the bottom of the east basin. Among them, one depression was located near the east shore of the lake. In the depression, we confirmed a discharge of hot water. The hot water contained high concentrations of CO2 and HCO3‾. It was estimated that the hot water was always accompanied by bubbles at the lake bottom. The bubbles at the depression were thought to have risen toward the chemocline developed at −50 m, and generated a slow updraft of lake water. The raising bubbles could be, for example, the “pilot light” of limnic eruption. The updraft flow of lake water at the chemocline initiated the CO2 degassing. An ascending current driven by the degassed CO2 bubbles entrained the lake water deeper than the chemocline, and the subsequent degassing of CO2 in lake water amplified the ascending current, causing the 1984 limnic eruption. The 1984 limnic eruption produced strong waves to impact the lake’s eastern shore, causing a landslide on the part of the shore and depositing it on the lake bottom; thereby, forming a mound. In another depression located near the south shore of the lake, no hot CO2-rich water was discharged. There was also a mound near the depression, implying a trace of another limnic eruption older than 1984. The west and central basins are shallow, and the layer deeper than −33m was a hypolimnion. The CO2 dissolved in the hypolimnion in 2015 seems to be the remains of CO2 brought in from the eastern basin until 2003 when the artificial degassing pipe began to function in the eastern basin.